Support system to allow powered wheelchair users to comfortably climb steps in their chairs. (2018) - Kaede, Kazunori; Otsuka, Ryohei; Watanuki, Keiichi; Muramatsu, Keiichi
It is difficult for electric wheelchair users who suffer from quadriplegia or have compromised motor skills to finely manipulate a joystick. In addition, they risk losing control of the wheelchair upon impacts with steps. In this paper, we describe a system we designed to assist users in finely controlling their speed, depending on the height of the step. The system incorporates a laser range finder to remotely detect the step. During testing, we evaluated the effects of exposing the user to whole-body vibrations in order to estimate the discomfort that arose from the step height and climbing speed. We also verified that this system reduced the impact caused by collisions with steps.